Desarrollo testicular y su relación con la calidad seminal en caprinos cruza Anglo Nubian x Boer (Nubor) - Puente, Marcos (2022)
The aim of this study was to monitor body weight and testicular development from weaning to one year of age, as well as to determine the relationship between body weight, scrotal circumference and sperm quality of Nubor crossbred goats. Body weight and scrotal circumference measurements were made from weaning (3 months) every 30 days until 12 months of age. After 12 months, the evaluation of sperm quality (ejaculate volume, sperm concentration and total sperm) began. Body weight was 24 ± 2.45 kg and scrotal circumference was 18.6 ± 1.14 cm at weaning and 60.3 ± 7.80 kg and 28.3 ± 1.56 cm at 12 months, respectively, indicating a positive linear relationship between age and weight, and a polynomial relationship. second degree between weight and scrotal circumference. A positive and strong correlation was found between scrotal circumference with weight (r = 0.89) and with sperm concentration (0.84), but not significant with ejaculate volume.